Internet English : www-based communication activities - Gitsaki, Christina; Taylor, Richard P. (New York : Oxford University Press, 1999)
Computers today. Surfing the web. Electronic mail. Famous people. Web cards. Study abroad. Eating out. Shopping spree. Watching movies. Vacation abroad. Cyber C@fes. Working abroad. News online...
Keywords: English language; Internet; International communication; Computer network; English language -- Textbooks for foreign speakers; Internet (Computer network) -- Problems, exercises, etc; World Wide Web (Information retrieval system) -- Problems, exercises, etc; Communication, International -- Problems, exercises, etc